Comparison of neural networks for suppression of multiplicative noise in images - V.A. Pavlov; A.A. Belov; V.T. Nguen; N. Jovanovski; A.S. Ovsyannikova (Компьютерная оптика)
The paper compares several neural network (NN) architectures for suppression of multiplicative noise. The images may contain sharp boundaries and large homogeneous areas. Convolutional and fully connected networks are investigated. It is shown that different architectures require significantly different amount of training data to reach the same noise suppression quality. Examples of NN requiring lower amounts of training data are presented.